2006
DOI: 10.1016/j.jvs.2005.11.063
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the aortic bifurcation: Branched endovascular grafts for thoracoabdominal and aortoiliac aneurysms

Abstract: Branch vessel technology has made it technically feasible to preserve critical end-organ perfusion in the setting of CIA, SRA, and TAA aneurysms. The relatively low acute mortality rate and lack of short-term branch vessel loss are encouraging and merit further investigation. These advances have the potential to markedly diminish the complications associated with conventional management of complex aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
192
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(198 citation statements)
references
References 31 publications
3
192
0
3
Order By: Relevance
“…2) In the territory of arch vessels, Larzon introduced "top fenestrated technique," wherein the circulation into LCA and left subclavian arteries were maintained similarly. 3) Ohrlander proposed the term "chimney graft" when covered stents were employed in a similar fashion.…”
Section: Discussionmentioning
confidence: 99%
“…2) In the territory of arch vessels, Larzon introduced "top fenestrated technique," wherein the circulation into LCA and left subclavian arteries were maintained similarly. 3) Ohrlander proposed the term "chimney graft" when covered stents were employed in a similar fashion.…”
Section: Discussionmentioning
confidence: 99%
“…8 The Cleveland clinic team has a high level of experience in endografting and has indicated that assessment by a 3D-CT workstation including CLF measurements play an important role in fenestrated and branched endograft design for complex aortic aneurysms. 10,11 Our institute does not have a large number of patients for endovascular treatment, compared with large hospitals in the USA. We applied the 3D workstation to plan 'regular' infrarenal devices in order to obtain excellent results for EVAR in an institute with a small number of patients with AAA.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Specialists in EVAR for complex aortic aneurysm have reported design and planning of fenestrated stent grafts and branched stent grafts using 3D-CT workstations. 10,11 The purpose of the current study was to evaluate the usefulness of using a 3D-CT workstation for planning EVAR in an institute with a small number of patients.…”
mentioning
confidence: 99%
“…In this systematic review, 12 studies included five reports of [64]. Technical success rates for iliac branch devices have been reported as greater than 95 % in several publications, with a clear improvement after the advent of newer generation devices [65][66][67][68][69][70][71]. A systematic analysis by Karthikesalingam and associates [72] included 196 patients treated with IBDs, with technical success rates ranging from 85 to 100 %, with no aneurysm-related deaths.…”
Section: Several Reports Frommentioning
confidence: 99%